Validity and reliability of a virtual education satisfaction questionnaire from the perspective of cardiology residents during the COVID-19 pandemic - Behshid Ghadrdoost; Parham Sadeghipour; Ahmad Amin; Hooman Bakhshandeh; Feridoun Noohi; Majid Maleki; Mohammad Mehdi Peighambari; Majid Haghjoo; Mohammad-Javad Al; Mohammad Sadeghvashveshady; Bahram Mohebbi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has prompted the further virtualization of medical education. The satisfaction level of specific users such as cardiology residents with virtual education can augment its quality; hence, the significance of a valid and reliable questionnaire to obtain feedback is needed. This study aimed to design and measure validity and reliability of a satisfaction questionnaire for virtual education of cardiology residents during COVID-19 pandemic. MATERIALS AND METHODS: In this cross-sectional study, a self-administered questionnaire was developed by the faculty members of Rajaie Cardiovascular Medical and Research Center. Reliability was tested utilizing Cronbach's alpha and intercorrelation which was tested using Pearson's correlation coefficient test (ICC). Factor analysis was done by the Kaiser-Meyer-Olkin measure of sampling adequacy and Bartlett's sphericity test. The statistical analyses were performed with the SPSS software version 22. RESULTS: The face validity index was determined via an assessment of the relevance, clarity, and simplicity of each item, and values >0.79 were accepted. The total Cronbach's alpha coefficient was calculated 0.93. Concerning test-retest reliability, the correlation between two rounds of evaluation was >80 (P > 0.001) and ICC was 0.99 (P = 0.001). The content validity evaluation yielded an index of 0.95 and a ratio of 0.91. The principal component factor analysis, conducted to investigate construct validity, generated four domains. CONCLUSIONS: The study results confirmed the validity and reliability of the designed questionnaire to evaluate the level of satisfaction of cardiology residents with virtual learning in COVID-19 pandemic.